The Role of Augmented Reality-Based Inquiry Learning in Enhancing Elementary Students’ Scientific Literacy for Sustainable Quality Education - Amandus Yonatan; Haratua Tiur Maria Silitonga; Afandi; Dede Suratman; Elvi Rusmiyanto Pancaning Wardoyo; Muhammad Zaidi Zakaria (Postgraduate, University of Mataram, 2026)
This study examined the effect of an Augmented Reality (AR)-supported inquiry learning model on elementary school students’ scientific literacy. This study employed a quasi-experimental non-equivalent group design involving two instructional groups: an experimental group receiving AR-supported inquiry learning and a comparison group receiving guided inquiry learning without AR support. Data were collected through scientific literacy pretests and posttests administered to both groups. The findings showed that the experimental group achieved greater improvement in scientific literacy, with mean scores increasing from 64.71 to 78.63, whereas the guided inquiry group showed a smaller increase from 52.66 to 55.10. Paired-sample t-test results indicated a significant improvement in the experimental group (p < .05), while the guided inquiry group did not demonstrate a statistically significant change (p > .05). In addition, an independent-samples t-test revealed a significant difference between the two groups after treatment (p < .05). Effect size analysis produced a Cohen’s d value of 0.95, indicating a large practical effect. These findings suggest that AR-supported inquiry learning is more effective than guided inquiry learning without AR support in enhancing elementary school students’ scientific literacy.